Design and implementation of electric cloud's resource pool - Ning YANG; Huayong LUO; Xing LI; Feng SHANG; Tao CHEN; Guoxia WANG (Dianxin kexue)
Cloud computing promotes the information construction and becomes an inevitable choice for electric enterprise.How to make cloud computing land is a huge problem for electric enterprise.The concept of electric cloud was proposed and it was confirmed that resource pool was one of the technologies to make cloud computing land in electric enterprise. According to the characters of electric enterprise, the designing principle about the capacity and the base schema of resource pool was proposed.And the implementation plans of the resource pool were given.The key factors of resource pool and their assembling methods can be known clearly form the base schema of resource pool,there is great practical importance on the planning and strategy of resource pool.